2021
DOI: 10.1136/bmjopen-2021-050995
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry adoption and oxygen orders at paediatric admission over 7 years in Kenya: a multihospital retrospective cohort study

Abstract: ObjectivesTo characterise adoption and explore specific clinical and patient factors that might influence pulse oximetry and oxygen use in low-income and middle-income countries (LMICs) over time; to highlight useful considerations for entities working on programmes to improve access to pulse oximetry and oxygen.DesignA multihospital retrospective cohort study.SettingsAll admissions (n=132 737) to paediatric wards of 18 purposely selected public hospitals in Kenya that joined a Clinical Information Network (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Time elapsed was captured as months since the hospitals joined the CIN-N and was treated as a continuous fixed effect. From previous studies within the CIN, the effect of time on adherence to recommended clinical practice was found to vary across hospitals [28]. We used a likelihood ratio test (LRT) to determine the most suitable random effects model (hospital random intercepts vs hospital random intercepts with random slopes for time).…”
Section: Methodsmentioning
confidence: 99%
“…Time elapsed was captured as months since the hospitals joined the CIN-N and was treated as a continuous fixed effect. From previous studies within the CIN, the effect of time on adherence to recommended clinical practice was found to vary across hospitals [28]. We used a likelihood ratio test (LRT) to determine the most suitable random effects model (hospital random intercepts vs hospital random intercepts with random slopes for time).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a retrospective study of pulse oximeter use in pediatric patients at 18 Kenyan hospitals found that 8.6% of patients had oxygen prescribed, but 87% of patients either did not have pulse oximetry performed or did not have oxygen saturations lower than 90%. 55 In situations where oxygen supply is limited, liberal and nontitrated dosing of supplemental oxygen may lead to or exacerbate supply shortages. In a study of patients in the adult emergency department of a Rwandan teaching hospital, Sutherland and colleagues found that 12% of patients were hypoxemic, but on over 80% of days, patients were either over or undertreated with oxygen to achieve a target oxygen saturation of 90% to 95%.…”
Section: Global and Public Health Impactmentioning
confidence: 99%
“…Time elapsed was captured as months since the hospitals joined the CIN-N and was treated as a continuous fixed effect. From previous studies within the CIN, the effect of time on adherence to recommended clinical practice was found to vary across hospitals [28]. Likelihood ratio tests (LRT) were used to determine the most suitable random effects model (hospital random intercepts vs hospital random intercepts with random slopes for time).…”
Section: Plos Global Public Healthmentioning
confidence: 99%